2017
DOI: 10.1080/00016357.2016.1278079
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the Turkish version of the Rapid Estimate of Adult Literacy in Dentistry (TREALD-30)

Abstract: TREALD-30 showed satisfactory psychometric properties. It may be used to identify patients with low OHL. Socio-demographic factors, oral health behaviors and health literacy skills should be taken into account when planning future studies to assess the OHL in both clinical and community settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 36 publications
5
40
1
1
Order By: Relevance
“…Similar to previous validation studies, the translation and adaptation processes were strictly based on established guidelines; in addition, useful comments from the 3 representatives from the pilot test were considered through a face validity discussion. Regarding the small sample size of 160 in this study, prior studies have noted that the number of respondents should be between 2 and 20 per item for a total of 100‐250 study participants. The HeLD‐Th has 14 items; thus, 28‐280 respondents are recommended.…”
Section: Discussionsupporting
confidence: 85%
“…Similar to previous validation studies, the translation and adaptation processes were strictly based on established guidelines; in addition, useful comments from the 3 representatives from the pilot test were considered through a face validity discussion. Regarding the small sample size of 160 in this study, prior studies have noted that the number of respondents should be between 2 and 20 per item for a total of 100‐250 study participants. The HeLD‐Th has 14 items; thus, 28‐280 respondents are recommended.…”
Section: Discussionsupporting
confidence: 85%
“…Also a summary of the quality of the domains examined on the basis of a checklist COSMIN for oral health assessment tools reported in the Supplementary material 3. The results of methodological quality evaluation of the tools showed that, out of the 21 tools examined, 9 tools at least in one dimension were in the category of poor, which indicated the poor quality of that area [33-35, 37-41, 43, 49].The results of tool review using the COSMIN checklist showed that, 19 studies at least in one dimension had a "fair" quality, which indicated the suspected methodological quality [32,33,[35][36][37][38][39][40][42][43][44][45][46][47][48][49][50][51][52]. Also, 20 and 4 articles at least in one dimension had a "good" [32,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] and "excellent" [37,39,47,…”
Section: Resultsmentioning
confidence: 99%
“…Four tools, by examining seven domains, had paid the most attention to the domains in the psychometric section [39,45,[47][48][49], and the two tools of ToFHLiD and OHLA-B had evaluated the minimum domains in the COSMIN checklist [33,50].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reporting the development of OHL instruments have used samples sizes in the range of 100-200 participants [14,[23][24][25][26][27]. Specifically, previous reports of the development of REALD-99 [13] and REALD-30 were based upon sample sizes of 102 and 202 adults [14], respectively.…”
Section: Study Populationmentioning
confidence: 99%
“…It was also noted that 23 of 29 OHL reviewed studies were conducted in the United States-European studies investigating OHL as an oral health determinant are generally scarce, in spite of almost half of Europeans are known to have inadequate or problematic health literacy skills [22]. The most commonly used OHL instrument is REALD-30-a word recognition scale that has been adapted for use in several languages other than English [23][24][25][26][27], but not Greek. In fact, currently no Greek language OHL measurement instrument exists.…”
Section: Introductionmentioning
confidence: 99%